Bringing a structural perspective to work: Framing occupational safety and health disparities for nursing assistants with work-related musculoskeletal disorders. - Haas, Alysa D.; Hunter, Daniel A.; Howard, Ninica L. (Work, 2018)
BACKGROUND: Certified Nursing Assistants (CNAs) experience a high risk of work-related musculoskeletal disorders (WMSDs) and are further made vulnerable by their situation in low levels of workplace and societal hierarchies of power and privilege. OBJECTIVE: This study applies structural vulnerability theory to CNA WMSD experiences in order to identify structural factors that may influence such injuries. METHODS: A sample of CNAs (n = 26) working in Nursing and Residential Care Facilities (NRCFs) was selected from workers who filed a claim during 2011–2014 for a WMSD of the back, shoulder, knee, or hand/wrist in the Washington State Department of Labor & Industries workers' compensation system. Interviews included questions about workers' injury experiences and work contexts. Qualitative data was analyzed for themes related to structural vulnerability theory and occupational safety and health (OSH) models. RESULTS: Themes illustrate a work environment in NRCFs with major organizational deficiencies for CNA safety and a broader structural environment that appears to mediate them. CNAs described policies and practices that result from management priorities being diverted away from worker safety. These difficulties are compounded by several aspects of CNAs' socio-economic vulnerability. CONCLUSIONS: This study demonstrates the utility of a structural perspective for OSH disparities research and points to the need for occupational health intervention on a structural level.